2020
DOI: 10.1136/bmjnph-2019-000042
|View full text |Cite
|
Sign up to set email alerts
|

Randomised double-blind placebo-controlled intervention study on the nutritional efficacy of a food for special medical purposes (FSMP) and a dietary supplement in reducing the symptoms of veisalgia

Abstract: ObjectiveTo assess whether the symptoms of veisalgia can be reduced by intense water supply and the intake of antioxidative supplements and plant extracts.MethodsWe performed the world’s largest randomised double-blind placebo-controlled intervention study (214 participants) on the efficacy of a food for special medical purposes (FSMP) against veisalgia symptoms. We analysed the effectiveness of: (1) an FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although Lieb and Schmitt ( 2020 ) found that the minerals may confer little or no effect in alleviating the ethanol‐induced side effects, their significant effects on repression of post‐alcohol symptoms have been reported by other scientists. In this contribution, selenium (Se), zinc (Zn), magnesium (Mg), copper (Cu), and vanadium (V) were reported to deliver the most effects in reducing the ethanol‐hangover symptoms (Min et al, 2010 ).…”
Section: Alleviation Of Ethanol‐induced Injuries and Hangover Symptom...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although Lieb and Schmitt ( 2020 ) found that the minerals may confer little or no effect in alleviating the ethanol‐induced side effects, their significant effects on repression of post‐alcohol symptoms have been reported by other scientists. In this contribution, selenium (Se), zinc (Zn), magnesium (Mg), copper (Cu), and vanadium (V) were reported to deliver the most effects in reducing the ethanol‐hangover symptoms (Min et al, 2010 ).…”
Section: Alleviation Of Ethanol‐induced Injuries and Hangover Symptom...mentioning
confidence: 99%
“…Similar study conducted by Noh et al ( 2009 ) found that Dandelion juice could increase the concentrations of plasma ALDH and expression of catalase and glutathione reductase in males aged 24–28 years. Alleviation of hangover symptoms was also studied by Lieb and Schmitt (Lieb & Schmitt, 2020 ) in healthy adult individuals by administration of a formula containing Malpighia glabra fruit extract, Opuntia ficus indica fruit extract, Ginkgo biloba leaf extract, Salix alba leaf extract, and Zingiber officinale root extract enriched with vitamins and minerals. To understand the detoxification effects of plant extract, a second group delivered a supplement that contained vitamins and minerals in the absence of the plant extracts.…”
Section: Alleviation Of Ethanol‐induced Injuries and Hangover Symptom...mentioning
confidence: 99%
See 1 more Smart Citation
“…To combat these disease, researchers in most countries have used foods to develop different regimens for patients FSMP. Part of the treatments have involved use of specially processed formula foods, which meet the special needs of nutrition or diet for people with restricted eating, digestion and absorption disorders, as well as metabolic disorders and specific diseases (20). At present, some theoretical studies and programs have been designed for clinical practice.…”
mentioning
confidence: 99%